Land degradation and climate change: building climate resilience in agriculture. Issue 8 (5th September 2017) - Webb, Nicholas P; Marshall, Nadine A; Stringer, Lindsay C; Reed, Mark S; Chappell, Adrian; Herrick, Jeffrey E
Abstract : Land degradation and climate change pose enormous risks to global food security. Land degradation increases the vulnerability of agroecological systems to climate change and reduces the effectiveness of adaptation options. Yet these interactions have largely been omitted from climate impact assessments and adaptation planning. We examine how land degradation can influence climate‐change impacts and the adaptive capacity of crop and livestock producers across agroecological systems. We then present novel strategies for climate‐resilient agriculture that support opportunities to integrate responses to these challenges. Forward‐looking, climate‐resilient agriculture requires: (1) incorporation of land degradation processes, and their linkages with adaptive capacity, into adaptation planning; (2) identification of key vulnerabilities to prioritize adaptation responses; (3) improved knowledge exchange across local to global scales to support strategies for developing the adaptive capacity of producers; and (4) innovative management and policy options that provide multiple "wins" for land, climate, and biodiversity, thus enabling global development and food security goals to be achieved.